Analysis of sonographic features of endometrial diseases in postmenopausal asymptomatic women - Surkont, Grzegorz; Wlaźlak, Edyta; Bitner, Adam; Tyliński, Wiesław; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: Nowadays there are studies which aim is detection of endometrial cancer screening tool. A lot of attention is given to transvaginal ultrasound (TVS). The aim of the study was to estimate usefulness of TVS in detection endometrial neoplasms in postmenopausal asymptomatic women and to evaluate ultrasonografic features of endometrial diseases. Materials and methods: We analyzed 620 postmenopausal asymptomatic women who were non-users of HRT. TVS was evaluated by two physicians with big gynecologic ultrasound experience. In 57 patients (group I) we detected suspicious ultrasound picture of endometrial cavity. This was verified by D&C and histopathological assessment. Second group (n=563) was determined by postmenopausal women who had invasive diagnostic because of abnormal uterine bleeding. Results: In first group of patients we detected endometrial carcinoma in 8.77% cases, simple hyperplasia without atypia – 5.26%, endometrial polyp – 22.81%. In 63.16% of women we did not detect any endometrial disease. In second group as a result of D&C and histopathological exam we found in 3.92% cases endometrial carcinoma, 0.53% – simple hyperplasia without atypia, 1.42% – complex hyperplasia without atypia, 0.89% – complex hyperplasia with atypia, 0.89% – endometrial polyp. In 92.36% of women we did not detect any endometrial disease. Conclusions: TVS seems to be helpful in endometrial carcinoma detection among postmenopausal, asymptomatic women. Most useful parameter is fluid and solid masses in endometrial cavity. There is need to perform prospective, multicenter studies on big number of patients to evaluate real usefulness of TVS in endometrial carcinoma detection.